A Short Theoretical Note on Optical Absorption of Amorphous Gallium Arsenide in the Infrared Range - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
An approach to determine the optical absorption coefficient of amorphous GaAs in the far infrared range is developed. Results from this approach are compared with experiment and with other theoretical results. In our formulation, contributions corresponding to both dynamical and structural disorders are taken into consideration.